STRATEGI PUSTAKAWAN DALAM PELAKSANAAN SHELVING KOLEKSI SEBAGAI UPAYA TEMU KEMBALI INFORMASI DI SMAN 2 TRENGGALEK - Fatoni, Muhammad Rizki; Handayani, Nurul Setyawati (Fihris: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Collection shelving activities involve arranging and organizing the existing collections within the library according to shelves and based on their classification codes. This study aims to examine the strategies of librarians in carrying out collection shelving to facilitate information retrieval at Senior High School 2 Trenggalek Library. This research employs a qualitative method based on a case study approach. Data will be obtained through interviews with librarians and some students to assess the success of shelving for information retrieval, involving 2 librarians. Data will also be obtained from direct observations of collection shelving practices at Senior High School 2 Trenggalek’s library, supported by documentation. In analyzing the data, Miles and Huberman’s theory, which consists of three stages: data reduction, data display, and conclusion, will be utilized. The findings of this study are divided into an overview of the research object, presentation of research data, and data analysis. The data analysis reveals that librarians employ various strategies in the implementation of shelving, including strategic placement procedures, grouping based on the Dewey Decimal Classification system, book labels (call numbers), and shelf labels, as well as the utilization of technology for easy information retrieval. However, challenges in the shelving process include damaged or detached book labels and shelf markers.